Electrodes and manufacturing method
Patent Information
- Application Number
- JP2024549456
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-02-23
- Filing Date
- 2023-02-23
- Publication Date
- 2025-03-13
AI Technical Summary
を実証する上での重要な結果である。
Smart Images

Figure 2025506746000009 
Figure 2025506746000010 
Figure 2025506746000011
Abstract
Description
[Technical field]
[0001] The present invention relates to electrodes comprising niobium oxide and methods of making such electrodes. Such electrodes are of interest for use as anodes in metal ion batteries, such as lithium ion or sodium ion batteries, preferably lithium ion batteries. [Background technology]
[0002] Lithium-ion (Li-ion) batteries are a type of commonly used rechargeable battery, with the global market predicted to grow to $200 billion by 2030. Li-ion batteries are the technology of choice for electric vehicles, which meet multiple requirements from technical capabilities to environmental impact, providing a viable path towards a greener automotive industry.
[0003] A typical lithium-ion battery consists of multiple cells connected in series or parallel. Each cell usually consists of an anode (negative electrode) and a cathode (positive electrode), separated by a porous, electrically insulating film (called a separator) and bathed in a liquid (called the electrolyte) that allows the transport of lithium ions. In most systems, the electrode consists of an active electrode material, meaning that it can chemically react with lithium ions to reversibly store and release them in a controlled manner, optionally mixed with conductive additives (such as carbon) and polymeric binders. A slurry of these components is coated as a thin film onto a current collector (usually a thin foil of copper or aluminum), thus forming the electrode when dried.
[0004] In conventional Li-ion battery technology, the safety limitations of graphite anodes during battery charging are a major obstacle to their application in high-power electronics, automobiles and industries. Various polymorphs of niobium oxide have been demonstrated as Li-ion battery materials in the past. In 1981, Reichman and Bard (B. Reichman and A. J. Bard, "The Application of Nb2O5 as a Cathode in Nonaqueous Lithium Cells", J. Electrochem. Soc., 128, 344, 1981) were the first to demonstrate the electrochemical performance of niobium oxide as a cathode material in lithium-ion batteries. Then, in 1983, Cava et al. (RJCava, DW Murphy, and SM Zahurk, "Lithium insertion in Wadsley-Roth phases Based on Niobium Oxide", J. Electrochem.Soc., vol.130, no.12, pp.2345-2351, 1983) studied the Wadsley-Roth phases of lithium inserted in niobium oxide. In 1994, Koshiba et al. (N.Koshiba, K.Takata, M.Nakanishi, and Z.Takehara, "Evaluation of crystalline Nb2O5 as an anode of rechargeable lithium cell", Denki Kagaku, vol.62, no.7, pp.593-601, 1994) studied different niobium oxide polymorphs from calcination of niobium chloride at different temperatures as anode materials for Li-ion batteries.More recently, Griffith et al. (KJGriffith, ACForse, JM Griffin, and C.P. Grey, "High-Rate Intercalation without Nanostructuring in Metastable Nb2O5 Bronze Phases", J.Am.Chem.Soc., vol.138, no.28, pp.8888-8899, 2016) studied various micro-sized niobium oxide polymorphs synthesized from heating NbO2 as an anode material and found that the capacity and rate performance of the low-temperature bronze phase TT and T polymorphs are intrinsic properties of the bulk crystal structure. Li et al. ("A Niobium Oxide with Shear Structure and Planar Defects for High-Power Lithium Ion Batteries", Energy Environ.Sci., 2021) prepared micrometer-sized H-Nb2O5 rich in Wadsley planar defects by tuning the calcination temperature for fast lithium absorption. Furthermore, they tested the effect of particle size on cell performance for well-crystallized H-Nb2O5, obtaining smaller particle sizes by roller milling. Cell results suggested that reducing the particle size showed little improvement. In WO2021 / 245411, niobium oxides are represented by the general formula M1. a M2 1-a M3 b Nb 12-b O 33-c-d EP0402687B1 describes a fluorine-containing fluoride having a fluorine value of <1000 ppm, a weight percent of >99.9, a sieve pass through a 45 μm mesh and a BET surface area of 3.5 m 2 / g and for niobium oxide powders with >90% T phase for ceramic capacitor applications.
[0005] In summary, niobium oxides, although possessing some promising properties, are said to have inherently poor electronic conductivity and capacity fade issues due to shattering during charging and discharging, which limit their practical application in lithium-ion batteries. Specifically, the Wadsley-Roth H-Nb2O5 polymorph exhibits the highest specific capacity but the lowest capacity retention at high charge and discharge rates due to increased impedance (see polarization) effects. Meanwhile, the low-temperature bronze polymorphs T-Nb2O5 and TT-Nb2O5 exhibit higher capacity retention at high charge and discharge rates but suffer from low specific capacity. More reduced forms of niobium oxides, such as NbO2, can exhibit significant increases in electrical conductivity as the material becomes semiconducting, but the ability to insert Li-ions is lost as the material no longer bears the Wadsley-Roth or bronze crystal structure type considered to be favorable. Typical approaches to address these issues rely on extensive nanoscale or particle-level engineering, increasing the complexity of fabrication. Thus, more efficient methods of optimizing niobium oxides for use as active electrode materials are still needed. Summary of the Invention
[0006] In a first aspect, the present invention provides a method of making an electrode, the method comprising providing a starting material, H-Nb2O5, jet milling the starting material and classifying it to obtain a niobium oxide having a D of 2.2 to 15 μm. 50 Particle size, and a particle size distribution span (D 90 ~D 10 ) / D 50 and forming an electrode including the treated H—Nb2O5 material as an active electrode material.
[0007] Processing H-Nb2O5 using jet milling and classification to achieve specific particle size parameters has been found to provide surprising improvements when compared to the use of other milling methods and other particle size parameters. For example, as shown by this example, control of the milling method and particle size distribution of the processed H-Nb2O5 material enhances the capacity of H-Nb2O5 when functioning as an active electrode material, even when delithiated at high rates, e.g., 5C and 10C. These are important results in demonstrating the advantages of the present invention for providing electrodes for use in high power batteries designed for high rate charging and discharging.
[0008] In a second aspect, the present invention provides a method of making an electrochemical cell, the method comprising making an electrode by following the method of the first aspect and forming an electrochemical cell comprising the electrode. Preferably, the electrode forms the anode of the electrochemical cell. Preferably, the electrochemical cell is a metal ion battery, such as a lithium ion battery or a sodium ion battery, most preferably a lithium ion battery.
[0009] The present invention provides an electrode and an electrochemical cell resulting from the first and second aspects. [Brief description of the drawings]
[0010] [Figure 1] 1 shows particle size distributions in Examples 1 to 6. [Diagram 2] 1 shows XRD data for Examples 1 to 6. [Diagram 3] 1 is a SEM of powders of Examples 1, 2, 5, and 6. [Figure 4] 1 is a SEM of electrodes obtained using powders of Examples 1, 2, and 6. [Diagram 5] 4 shows particle size distributions of Examples 7 to 9. [Figure 6] 1 shows SEM images of powders of Examples 7 to 9. [Figure 7] 1 shows SEM images of electrodes obtained using the powders of Examples 7 to 9. [Figure 8]1 shows XRD of Examples 7 to 9. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The starting material used in this process is H-Nb2O5, a polymorph of Nb2O5 with the Wadsley-Roth crystal structure. The Wadsley-Roth crystal structure is believed to be a crystallographic off-stoichiometry of the MO3(ReO3) crystal structure with crystallographic shear, and has the simplified formula MO 3-x As a result, these structures usually contain octahedral subunits of [MO6] along with other subunits in the crystal structure. The H-Nb2O5 crystal structure has an array of octahedral units arranged in a block structure, with (3×4)1 and (3×5) ∞ The Nb2O5 crystal structure includes a combination of ReO3-like blocks of 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87, 88, 90, 91, 92, 93, 94, 95, 96, 97, 98, 99, 100, 101, 112, 126, 130, 140, 150, 160, 170, 182, 197, 199, 103, 114, 128, 136, 140, 151, 166, 170, 187, 199, 19
[0012] The starting material H-Nb2O5 may have a phase purity of >80 wt% H-Nb2O5, >90 wt% H-Nb2O5, or >95 wt% or about 100 wt% H-Nb2O5. Phase purity refers to the proportion of Nb2O5 that adopts the H-Nb2O5 crystal structure as opposed to other crystal structures of Nb2O5. Phase purity may be determined by X-ray diffraction. The starting material H-Nb2O5 may be substantially pure H-Nb2O5 or may include unavoidable impurities resulting, for example, from the manufacturing process. The starting material H-Nb2O5 may be doped with additional cations and / or anions, provided that the crystal structure corresponds to that of H-Nb2O5. The term "corresponding" may be understood to mean that the peaks in the X-ray diffraction pattern may be shifted by 0.5 degrees or less (preferably by 0.25 degrees or less, more preferably by 0.1 degrees or less) from the corresponding peaks in the reference X-ray diffraction pattern.
[0013] The starting material H-Nb2O5 may be obtained from a commercial supplier. Alternatively, the starting material H-Nb2O5 may be made by annealing niobium oxide precursors (e.g., NbO2, Nb2O5, other polymorphs of Nb2O5 hydrate) in air at above 900°C, e.g., 1100°C-1300°C. The formation of H-Nb2O5 may then be confirmed by XRD. The annealing time may be at least 30 minutes, or at least 1 hour. The starting material is typically obtained with relatively large grain sizes that are not suitable for use as an active electrode material. For example, the starting material H-Nb2O5 may have a D of >20 μm, 25-150 μm, or 30-100 μm. 50 It may have a particle size.
[0014] The term "particle size" refers to the equivalent spherical diameter (esd), i.e., the diameter of a sphere having the same volume as a given particle, the volume of a particle being understood to include the volume of any intra-particle pores. n " and "D n The term "particle size" refers to the diameter below which n% by volume of the particle population is found. 50 " and "D 50The term "particle size" refers to the volume-based median particle size below which 50% by volume of the particle population are found. It will be understood that where the material contains primary crystallites aggregated into secondary particles, the particle size refers to the diameter of the secondary particles. Particle size can be measured by laser diffraction. Particle size can be measured, for example, using Mie theory in accordance with ISO 13320:2009.
[0015] The starting material H-Nb2O5 typically has a relatively small surface area. For example, the starting material has a surface area of <0.8 m 2 / g or <0.6m 2 The BET surface area may be 100 / g. The term "BET surface area" refers to the surface area per unit mass calculated from the measurement of the physical adsorption of gas molecules on a solid surface using the Brunauer-Emmett-Teller theory. For example, the BET surface area can be measured according to ISO9277:2010.
[0016] The starting material H-Nb2O5 is jet milled and classified. Jet milling is a powder grinding technique in which powder material is accelerated by high pressure gas or steam, causing interparticle collisions to reduce particle size. Two common designs are spiral jet mills and fluidized bed jet mills. Spiral jet mills usually have a cylindrical grinding chamber with several gas nozzles arranged tangentially. The selection of particle size is made by the aerodynamic properties of the particles and the spiral design, which allows good control of fineness. Fluidized bed jet mills usually have a grinding chamber in which gas nozzles are arranged radially in the chamber wall to form a fluidized bed. Jet mill grinding may include fluidized bed jet mill grinding. Jet mill grinding may be achieved without the use of spiral jet mill grinding (e.g., it may consist of fluidized bed jet mill grinding).
[0017] Classification is typically achieved by air classification, such as, for example, using a centrifugal forced vortex air classifier. The desired particle size distribution can be achieved by controlling process parameters such as, for example, centrifugal force and suction force to filter out powders of a particular particle size.
[0018] Other common methods of powder grinding are impact milling and high shear milling. In impact milling, powder materials are milled by mechanical impact with high velocity components, which can be gravitational energy (hammer mills), or kinetic energy (high speed rotors / stators / pins, etc.). High shear milling consists of a rotating vessel or rotor, so the grinding components and powder materials interact with shear forces to reduce particle size.
[0019] In contrast to other powder grinding methods, jet milled and classified material can be identified by SEM. Specifically, SEM images of jet milled and classified material with particle size parameters defined herein are homogenous and free of very fine and larger particles that may be expected in SEM images of other ground materials. Electrodes containing the processed H-Nb2O5 material can be identified as having a homogenous surface free of large cavities and large particles.
[0020] The processed H-Nb2O5 material has a D of 2.2-15 μm, or optionally 2.5-12 μm, 3.0-10 μm, or 4.0-8.0 μm. 50 It has a particle size.
[0021] The processed H-Nb2O5 material has a particle size distribution span (D) of <1.90, or optionally <1.80, <1.60, or <1.50. 90 ~D 10 ) / D 50 For example, the particle size distribution span (D 90 ~D 10 ) / D 50 may be in the range of >0.2 to <1.90 or >0.5 to <1.50.
[0022] For materials processed by jet milling and classification, D within the specified ranges defined herein 50The combination of particle size and span has been found to enhance the properties of H-Nb2O5 for use as an active electrode material. For example, as shown by this example, there is a significant improvement in capacity at high delithiation rates, e.g., 5C and 10C, compared to alternative particle size parameters and milling methods. It is theorized that the particle size and distribution of the active electrode material directly impacts Li-ion cell performance in several ways: 1) Electrical conductivity. Active electrode materials with larger particle size and broad distribution lead to non-uniform electrodes and impaired processability at industrial scale, e.g., by roll-to-roll coating processes, resulting in poor electronic conductivity and inconsistent performance of the electrode. Additionally, larger particle size results in longer diffusion paths for Li-ions, leading to poor cell performance at high rates. 2) Side reactions. Active electrode materials with smaller particle size correspond to a high specific surface area, which leads to more undesirable side reactions with the electrolyte, leading to material degradation and short cycle life. The inventors have determined that the particle size and distribution of the active electrode material, which is designated D 50 It has been discovered that the particle size and particle size distribution span provide an optimal balance of these factors for H-Nb2O5. Furthermore, the use of jet milling and classification has been found to be a particularly advantageous method of achieving these parameters. Conventional size reduction techniques for powder materials include impact milling and high shear milling. However, these two types of milling are prone to inducing contamination due to direct contact of the powder with the milling media, and for particle sizes <20 μm, the control of particle size distribution is poor. Jet milling and classification avoids these issues, and the desired particle size parameters can be easily obtained by control of the processing parameters (e.g., centrifugal force and suction force). Thus, it has been found that the combination of particle size parameters achieved by jet milling and classification surprisingly improves the properties of H-Nb2O5 for use as an active electrode material.
[0023] An additional definition of the particle size distribution span is (D 95 -D5) / D 50 The processed H-Nb2O5 materials have particle size distribution spans (D 95 -D5) / D 50For example, the particle size distribution span (D 95 -D5) / D 50 may be in the range of >0.3 to <2.50 or >0.6 to <2.0.
[0024] The processed H-Nb2O5 materials have a D of >0.7μm, 1.0-8.0μm, or 1.5-4.0μm. 10 The processed H-Nb2O5 has a grain size of <30μm, 4.5-20μm, or 5.5-15μm D 90 The processed H-Nb2O5 material may have a grain size of >0.7m. 2 / g, or 1 to 20m 2 / g, or 0.8 to 2.50 m 2 / g BET surface area.
[0025] Following jet milling and classification, it is preferred that the H-Nb2O5 crystal structure be maintained. Thus, the processed H-Nb2O5 material may have a phase purity of >80 wt% H-Nb2O5, >90 wt% H-Nb2O5, or >95 wt% or about 100 wt% H-Nb2O5. The processed H-Nb2O5 material may be substantially pure H-Nb2O5. After jet milling and classification, there may be some change in the relative intensity of the characteristic peaks of the H-Nb2O5 crystal structure, which may be due to the introduction of defects in the crystal structure via the milling process. The intensity ratio of the peak at about 23.7° 2θ to the peak at about 24.4° 2θ in the XRD pattern of the processed H-Nb2O5 material may range from 0.7 to 1.3 or 0.8 to 1.2.
[0026] The treated H-Nb2O5 material is formed into an electrode such that the treated H-Nb2O5 material is an active electrode material. An active electrode material may be understood to mean a material capable of chemically reacting with lithium ions to reversibly store and release them in a controlled manner. The electrode is usually in the form of an electrode composition in electrical contact with a current collector. The current collector is usually a metal foil, such as, for example, copper or aluminum foil. The electrode may be made by forming a slurry of the treated H-Nb2O5 material and a solvent. The slurry may include at least one other component selected from a binder, a conductive additive, a different active electrode material, and mixtures thereof. The electrode composition may be formed on the current collector by depositing the slurry on the current collector and removing the solvent. Optionally, further steps may be performed, such as heat treatment to cure any binders, and / or calendaring of the electrode layer. For example, the solvent may be removed by drying, for example, at a temperature of 30-100°C. The electrode may have a density of 2-3.5 or 2.3-2.9 gcm -3 The electrode composition may form a layer having a thickness in the range of 5 μm to 2 mm, preferably 5 μm to 1 mm, preferably 5 μm to 500 μm, preferably 5 μm to 200 μm, preferably 5 μm to 100 μm, preferably 5 μm to 50 μm.
[0027] Alternatively, the slurry can be formed into a free-standing film or mat containing the active electrode material, for example, by casting the slurry onto a suitable casting template, removing the solvent, and then removing the casting template. The resulting film or mat is in the form of a coherent, free-standing mass, which can then be bonded to a current collector by known methods.
[0028] Optionally, the treated H-Nb2O5 material forms at least 10%, 50%, or 75% by weight of the total active electrode material in the electrode. The treated H-Nb2O5 material may form the only active anode material in the electrode.
[0029] The electrode composition may further include at least one other component selected from a binder, a conductive additive, a different active electrode material, and mixtures thereof. For example, one electrode composition includes about 92 wt. % of the treated H-Nb2O5 material, about 5 wt. % of a conductive additive (e.g., carbon black), and about 3 wt. % of a binder (e.g., poly(vinyl difluoride)), based on the total dry weight of the anode composition.
[0030] Examples of suitable binders include polyvinylidene fluoride and its copolymers (PVDF), polytetrafluoroethylene (PTFE) and its copolymers, polyacrylonitrile (PAN), poly(methyl)methacrylate or poly(butyl)methacrylate, polyvinyl chloride (PVC), polyvinyl formal, polyetheramide, polymethacrylic acid, polyacrylamide, polyitaconic acid, polystyrene sulfonic acid, polyacrylic acid (PAA) and its alkali metal salts, modified polyacrylic acid (mPAA) and its alkali metal salts, cellulosic polymers, carboxymethylcellulose (CMC), modified carboxymethylcellulose (mCMC), sodium carboxymethylcellulose (Na-CMC), polyvinyl alcohol (PVA), alginates and their alkali metal salts, butadiene acrylonitrile rubber (NBR), hydrogenated form of NBR (HNBR), styrene butadiene rubber (SBR), and polyimides. The binder may be present in the electrode composition at 0 to 30 wt%, or 0.1 to 10 wt%, or 0.1 to 5 wt%, based on the total dry weight of the electrode composition.
[0031] The conductive additive is preferably a non-active material included to improve the electrical conductivity between the active electrode materials and between the active electrode material and the current collector. The conductive additive may be appropriately selected from graphite, carbon black, carbon fiber, vapor grown carbon fiber (VGCF), carbon nanotubes, graphene, acetylene black, ketjen black, metal fiber, metal powder, and conductive metal oxide. Preferred conductive additives include carbon black and carbon nanotubes. The conductive additive may be present in the electrode composition in an amount of 0 to 20 wt%, 0.1 to 10 wt%, or 0.1 to 5 wt%, based on the total dry weight of the electrode composition.
[0032] The processed H-Nb2O5 material may be present in the electrode composition at 100-50 wt%, 99.8-80 wt%, or 99.8-90 wt%, based on the total dry weight of the electrode composition. When the active electrode material is present at 100 wt% of the electrode composition, it may form a solid electrode.
[0033] If a different active anode material is present in addition to the processed H-Nb2O5 material, it may be selected from lithium titanium oxide, titanium niobium oxide, oxides containing niobium and at least one other cation, graphite, hard carbon, soft carbon, silicon, doped versions thereof, and mixtures thereof.
[0034] The processed H-Nb2O5 material may undergo further processing after jet milling and classification and before forming the electrode. For example, the processed H-Nb2O5 material may be coated with carbon, for example to improve surface electronic conductivity and / or prevent reaction with the electrolyte. Processed H-Nb2O5 materials include aluminum oxides, zirconium oxides, oxides containing niobium and at least one other cation, organic or inorganic fluorides, organic or inorganic phosphates, titanium oxides, lithiated versions thereof, and mixtures thereof.
[0035] The invention includes the method of the first aspect, except that it omits the step of forming an electrode that includes the processed H-Nb2O5 material as an active electrode material. For example, the invention includes a method of making an active electrode material, the method comprising providing a starting material H-Nb2O5 and forming a crystalline H-Nb2O5 material having a particle size D of 2.2 to 15 μm. 50 and a particle size distribution span (D 90 -D 10 ) / D 50 and jet milling and classifying the starting material to provide a treated H-Nb2O5 material having a molecular weight of 0.1 to 0.25. The treated H-Nb2O5 material may then be used as an active electrode material in forming an electrode. The invention also includes the treated H-Nb2O5 material obtainable by this method.
[0036] The electrodes may be incorporated into an electrochemical cell. Preferably, the electrochemical cell includes the electrode as an anode, a cathode, and an electrolyte disposed between the anode and the cathode. The electrochemical cell is preferably a metal ion battery, such as a lithium ion battery or a sodium ion battery, and most preferably a lithium ion battery.
[0037] The electrochemical cell may be formulated to have an N / P ratio >1, where N / P is defined as:
number
[0038] The active fraction (wt %) is the proportion of the dry electrode composition that is the active material.
[0039] Initial lithiation / delithiation capacity (mAhg -1) is the specific capacity at C / 10 at 25° C. for the first lithiation cycle of the anode or the first delithiation cycle of the cathode measured in an equivalent half-cell with a Li metal counter electrode. An equivalent half-cell can be understood to utilize the same electrode composition deposited at the same area loading and active fraction as the full cell.
[0040] Cell charge rates are usually expressed as "C-rates". A 1C charge rate means a charge current such that the cell is fully charged in 1 hour, and a 10C charge means that the battery is fully charged in 1 / 10 of an hour (6 minutes). The C-rate may be defined in terms of the reversible capacity of the cell within the appropriate voltage limits, e.g., 1.0 mAh cm within voltage limits of 1.2 to 3.15 V. -2 For an anode with a capacity of 1.0 mA cm, the 1C rate is 1.0 mA cm. -2 corresponds to an applied current density of
[0041] The initial lithiation / delithiation capacity is measured on equivalent half-cells. For the anode, the initial constant current C / 10 lithiation (discharge, negative current) capacity (vs. Li / Li+) is measured at 25° C. For the cathode, the initial constant current C / 10 delithiation (charge, positive current) capacity (vs. Li / Li+) is measured at 25° C.
[0042] N / P may be in the range >1 to 2, or 1.01 to 1.5, or preferably 1.05 to 1.3. Alternatively, N / P may be ≦1, or <1, such as, for example, 0.7 to 0.95.
[0043] The cathode is LiNi 1-x M x The active cathode material may be selected from the O2 class of nickel-based layered oxides, where M=Co, Mn, Al, such as NMC (lithium nickel manganese cobalt oxide), NCA (lithium cobalt aluminum oxide), and LCO (lithium cobalt oxide), and LNMO (lithium nickel manganese oxide) (e.g., LiNi 0.5 Mn 1.5O4). Active cathode materials are widely available from commercial suppliers. The active cathode materials may be doped with additional cations and / or anions.
[0044] The choice of active electrode material may affect the range of suitable voltages, such as determining the initial lithiation / delithiation capacity. For example, suitable voltage ranges may be: LNMO: 5.2-3V, upper cutoff 5.2V; NCA, NMC, and LCO: 4.5-2.7V, upper cutoff 4.5V; processed H-Nb2O5 materials: 3-0V, lower cutoff 0V. Even narrower ranges may be: LNMO: 5-3V, upper cutoff 5V; NCA, NMC, and LCO: 4.3-2.7V, upper cutoff 4.3V; processed H-Nb2O5 materials: 3V-1.0V, lower cutoff 1.0V.
[0045] The range of suitable voltages may be determined experimentally. For example, the voltage profile correlates with the change in the energy state of the anode and cathode materials associated with the removal or insertion of electrons and ions. The cutoff voltage of the cell may be selected to fall before a certain inflection point in the voltage profile where the energy state of one or both electrodes rises above a critical level, causing the crystal structure to collapse into a lower energy structure at a rate significantly detrimental to the performance of the cell. The absolute voltage at which this occurs is a function of the electrode potentials of both electrodes, but can be calculated using a common reference electrode and does not need to be determined experimentally for well-established families of materials with reliable standard electrochemical behavior.
[0046] The cathode active material is preferably in particulate form, for example having a D in the range of 0.1 to 100 μm, or 0.5 to 50 μm, or 1 to 20 μm. 50 The particle size is:
[0047] The electrolyte may include any material suitable for the operation of a metal-ion battery, preferably a lithium-ion battery. For example, the electrolyte may be a non-aqueous solution (e.g., an organic electrolyte). The electrolyte may include one or more non-aqueous solvents and a salt at least partially dissolved in the solvent. For example, the solvent may include an organic solvent, such as ethylene carbonate (EC) and / or other carbonate-based solvents, or butyrate, or acetate, or a mixture thereof. The solvent may include 1M LiPF6 dissolved in an aprotic solvent mixture, such as a 1:1 weight ratio mixture of ethylene carbonate and other carbonate-based solvents or butyrate or acetate.
[0048] Salts suitable for use in the present invention include LiPF6, LiSbF6, LiBF4, LiTFSI, LiFSI, LiAlCl4, LiAsF6, LiClO4, LiGaCl4, LiC(SO2CF3)3, LiN(CF3SO2)2, Li(CF3SO3), LiB(C6H4O2)2, LiBOB (lithium bis(oxalato)borate), and LiDFOB (lithium difluoro(oxalato)borate). Suitable low viscosity solvents (e.g., organic solvents) for use in the electrolyte may include, but are not limited to, ethyl methyl carbonate (EMC), dioxolane (DOL), ethyl acetate (EA), propylene acetate (PA), butyl acetate (BA), methyl butyrate (MB), ethyl butyrate (EB), dimethyl carbonate (DMC), diethyl carbonate (DEC), 1,2-dimethoxyethane (DME), tetrahydrofuran (THF), methyl acetate (MA), diglyme (DGL), triglyme, tetraglyme, cyclic carbonates, cyclic esters, cyclic amides, propylene carbonate (PC), methyl propyl carbonate (MPC), acetonitrile, dimethyl sulfoxide (DMS), dimethylformamide, dimethylacetamide, gamma butyrolactone (GBL), and N-methylpyrrolidinone (NMP), as well as various mixtures or combinations thereof. EXAMPLES
[0049] Example 1 was obtained from a commercial supplier and was milled to obtain Examples 2-9.
[0050] Examples 2, 3, and 7-9 were produced in a fluidized bed jet mill with wheel classification (Alphane fluidized bed opposed jet mill AFG100 for Examples 2 and 7-9, AFG200 for Example 3).
[0051] Example 2 was milled at a pressure of 4.5 bar with a nozzle diameter of 2.5 mm. The classifier speed was set at 6000 rpm.
[0052] Example 3 was milled at a pressure of 6 bar with a nozzle diameter of 5 mm. The classifier speed was set at 6000 rpm.
[0053] Example 4 was made by spiral jet milling (MC DecJet® 100). The venturi pressure was set at 9 bar and the ring pressure was set at 8 bar. No classification was performed in this example.
[0054] Example 5 was made by rolling ball milling with zirconia balls in a 5L PTFE jar. The diameters of the milling balls are 5mm and 1mm. The material to ball ratio is 10:1. The rolling speed was 400 rpm. The milling time for 5A was 4 hours and the milling time for 5B was 12 hours.
[0055] Example 6 was made by impact milling (Retsch ZM200 impact mill) using the continuous milling method. The milling speed was set at 18000 rpm.
[0056] Example 7 was milled at a pressure of 5 bar with a nozzle diameter of 2.5 mm. The classifier speed was set at 8000 rpm.
[0057] Example 8 was milled at a pressure of 4 bar with a nozzle diameter of 2.5 mm. The classifier speed was set at 10000 rpm.
[0058] Example 9 was milled at a pressure of 4 bar with a nozzle diameter of 2.5 mm. The classifier speed was set at 3000 rpm.
[0059] The particle size distribution of the samples was measured using a Horiba Partica LA-960 equipped with a dry dispenser (Figures 1 and 5 and Table 1).
[0060] The surface areas were measured using BET surface area analysis with N2 at 77.35 K on a BELSORP-miniX instrument (Table 2). [Table 1] [Table 2]
[0061] Material characterization The phase purity of the samples was analyzed using a Rigaku Miniflex powder X-ray diffractometer at a scan rate of 1° / min in the 2θ range (10-70°) (Figures 2 and 8, and Table 3).
[0062] Example 1 was obtained as the starting H-Nb2O5 material with 100 wt% phase purity as determined by XRD. The XRD patterns of all milled examples (2-9) show that purity is maintained after milling. Differences in the relative intensities of two characteristic peaks at approximately 23.7° and approximately 24.4° 2θ are observed, which can be attributed to differences in the levels of defects introduced into the H-Nb2O5 crystal structure. [Table 3]
[0063] SEM results (Figures 3 and 6) showed that Example 1 had the most spherical particles with the largest particle size. The surface of these particles was composed of sintered primary particles. Example 2 showed the most uniformly sized particles. All particles in SEM were smaller than 15 μm. The particles of Example 5 showed a much broader size distribution compared to Example 2, with the largest particle being about 25 μm and the smallest particle being less than 1 μm. Example 6 showed the second largest particle size among the four examples imaged, with some particles being about 25 μm, indicating non-milled particles. Example 7 showed uniformly sized particles under SEM, with all particles being smaller than 12 μm. Example 8 showed a wide range of particle sizes, with particles larger than 20 μm and particles smaller than 10 μm. Example 9 showed a majority of large particles and occasional particles smaller than 5 μm. These results are consistent with the particle size distribution results obtained from laser diffraction shown in Table 1.
[0064] When made into electrodes (FIGS. 4 and 7), the powders with large grain sizes could not provide a uniform electrode surface. The surface of the electrode presented large cavities due to too much polymer binder (e.g., Example 1), damaging the electrical conductivity, or the large particles made the surface uneven (e.g., Example 6), damaging the cell's lifespan. The electrodes prepared from Examples 8 and 9 showed uneven surfaces with large cavities. In contrast, the electrode surfaces of Examples 2 and 7 were uniform and did not contain large particles.
[0065] Electrochemical characterization The charge rate of Li-ion batteries is usually expressed as "C-rate". A 1C charge rate means a charging current such that the cell is fully charged in 1 hour, while a 10C charge means that the cell is fully charged in 1 / 10 of an hour (6 minutes). The C-rate here is defined from the reversible capacity of the anode seen within the voltage limits applied in the second delithiation cycle, i.e., 1.0 mAh cm within the voltage limits of 1.1 to 3.0 V. -2 For an anode with a capacity of 1.0 mA cm, the 1C rate is 1.0 mA cm. -2For the typical materials described herein, this corresponds to an applied current density of about 215 mA / g active material.
[0066] Electrochemical testing was performed in half coin cells (CR2032 size) for analysis. In the half coin cell test, the active material is tested as an electrode against a Li metal electrode to evaluate the basic capabilities of the active material. In the following examples, the active material composition to be tested was combined with N-methylpyrrolidone (NMP), carbon black (Super P) acting as a conductive additive, and poly(vinyl difluoride) (PVDF) binder, and mixed into a slurry in a laboratory scale centrifugal planetary mixer. The non-NMP composition of the slurry was 92 wt% active material, 5 wt% conductive additive, and 3 wt% binder. The slurry was doctor blade coated onto an Al foil current collector at the desired coating weight of 69-75 g m. -2 The electrodes were then coated with 2.5–2.7 g cm−1 at 80°C and dried by heating. -3 The electrodes were then calendered to a density of 10 ...
[0067] The data are averaged from 3-5 cells prepared from the same electrode coating, with the errors shown as standard deviations. The data therefore represent robust research results that demonstrate the improvements achieved by the material according to the invention compared to conventional materials. These data are shown in Tables 4a and 4b. The first cycle coulombic efficiency is defined as the percentage of the capacity of the first lithiation step that is returned in the first delithiation step, and the generated capacity is defined as the capacity of the second delithiation step. [Table 4] [Table 5]
[0068] Consideration It has been found that Examples 2, 3, and 7, which have been jet milled and classified in accordance with the present invention, when incorporated into electrodes, provide improved capacity at all delithiation rates compared to the starting material of Example 1. In particular, Examples 2, 3, and 7 are superior to Example 4 (jet milled but not classified, and therefore has a higher particle size distribution span), Examples 5A and 5B (rolling ball milled), Example 6 (impact milled), Example 8 (jet milled and classified, but has a higher particle size distribution span), and Example 9 (jet milled and classified, but has a higher D 50 The capacity was improved at all delithiation rates compared to the niobium oxide active electrode material having a particle size of 10C. The improvement provided by the present invention is particularly evident at the high delithiation rates of 10C, a key result that demonstrates the utility of the present invention in providing niobium oxide active electrode materials for use in high power applications.
Claims
1. 1. A method of making an electrode, comprising the steps of: Starting material H-Nb 2 O 5 To prepare the following: The starting material is jet milled and classified to obtain a D of 2.2 to 15 μm. 50 Particle size, and a particle size distribution span (D 90 ~D 10 ) / D 50 The treated H-Nb 2 O 5 Providing materials and The treated H—Nb 2 O 5 forming an electrode including the material as an active electrode material; The method comprising:
2. The treated H—Nb 2 O 5 The material has a particle size distribution span (D 95 -D 5 ) / D 50 2. The method of claim 1, comprising:
3. The treated H—Nb 2 O 5 The material has a particle size distribution span (D 90 -D 10 ) / D 50 13. A method according to any preceding claim, comprising:
4. The treated H—Nb 2 O 5 The material has a D of 2.5 to 12 μm, 3.0 to 10 μm, or 4.0 to 8.0 μm. 50 13. The method of any preceding claim, wherein the particle size is 0.1 μm or less.
5. The treated H—Nb 2 O 5 The material has a D of >0.7 μm, 1.0-8.0 μm, or 1.5-4.0 μm. 10 13. The method of any preceding claim, wherein the particle size is 0.1 μm or less.
6. The treated H—Nb 2 O 5 The material has a D of <30 μm, 4.5-20 μm, or 5.5-15 μm. 90 13. The method of any preceding claim, wherein the particle size is 0.1 μm or less.
7. The treated H—Nb 2 O 5 Material: >0.7m 2 / g, or 1 to 20 m 2 / g, or 0.8 to 2.50 m 2 3. The method of any preceding claim, wherein the surface area of the crystalline silica is 0.1 to 1.0 μm.
8. The starting material H—Nb 2 O 5 D > 20 μm, 25-150 μm, or 30-100 μm 50 13. The method of any preceding claim, wherein the particle size is 0.1 μm or less.
9. The starting material H—Nb 2 O 5 The material is >80 wt.% H—Nb 2 O 5 , >90 wt.% H—Nb 2 O 5 or substantially pure H—Nb 2 O 5 13. A method according to any preceding claim, wherein:
10. The treated H—Nb 2 O 5 13. A method according to any preceding claim, wherein the intensity ratio of the peak at about 23.7° 2θ to the peak at about 24.4° 2θ in the XRD pattern of the material is in the range of 0.7 to 1.3 or 0.8 to 1.
2.
11. 10. A method according to any preceding claim, wherein the jet milling comprises fluidised bed jet milling or spiral jet milling, or comprises or consists of fluidised bed jet milling.
12. 10. A method according to any preceding claim, wherein said classification is achieved by a centrifugal forced vortex air classifier.
13. Forming the electrode comprises dissolving the treated H—Nb in a solvent. 2 O 5 10. The method of any preceding claim, comprising forming a slurry of material, depositing the slurry on a current collector, and removing the solvent.
14. 14. The method of claim 13, wherein the slurry comprises at least one additional component selected from a binder, a conductive additive, a different active electrode material, and mixtures thereof.
15. The treated H—Nb 2 O 5 10. A method according to any preceding claim, wherein a material is coated with carbon prior to forming the electrode.
16. The treated H—Nb 2 O 5 10. A method according to any preceding claim, wherein the material forms at least 10%, 50%, or 75% by weight of the total active electrode material within the electrode.
17. The treated H—Nb 2 O 5 10. A method according to any preceding claim, wherein the material is the only active electrode material in the electrode.
18. 13. The method of any preceding claim, further comprising forming an electrochemical cell including the electrode.
19. 20. The method of claim 18, wherein the electrochemical cell comprises the electrode as an anode, a cathode, and an electrolyte disposed between the anode and the cathode.
20. The electrochemical cell is formulated to have an N / P ratio >1, where N / P is: [0010] is defined as Area loading (mgcm -2 ) is the drying load of the electrode composition without considering the current collector, Active Fraction (wt %) is the fraction of the dry electrode composition that is the active material; Initial lithiation / delithiation capacity (mAhg -1 ) is the specific capacity at C / 10 at 25° C. for the first lithiation cycle of the anode or the first delithiation cycle of the cathode, measured in an equivalent half-cell with a Li metal counter electrode; 20. The method of claim 19.
21. The electrochemical cell is formulated to have an N / P ratio of ≦1, where N / P is [0025] is defined as Area loading (mgcm -2 ) is the drying load of the electrode composition without considering the current collector, Active Fraction (wt %) is the fraction of the dry electrode composition that is the active material; Initial lithiation / delithiation capacity (mAhg -1 ) is the specific capacity at C / 10 at 25° C. for the first lithiation cycle of the anode or the first delithiation cycle of the cathode, measured in an equivalent half-cell with a Li metal counter electrode; 20. The method of claim 19.
22. The method of any of claims 18 to 21, wherein the electrochemical cell is a metal ion battery, such as a lithium ion battery or a sodium ion battery, or the electrochemical cell is a lithium ion battery.
23. Electrode obtainable by the method according to any of the preceding claims.
24. Electrochemical cell obtainable by the method according to any of claims 18 to 22.